Isotopic niches reveal the trophic structure of the cetacean community in the oceanic waters around the Azores - Lebon, Myriam; Colaço, Ana; Prieto, Rui; Cascão, Irma; Oliveira, Cláudia; Tobeña, Marta; Planque, Yann; Spitz, Jérôme; Silva, Mónica A. (Frontiers in Marine Science, 2024)
Introduction The oceanic waters around the Azores host a high diversity of cetaceans, with 28 species of toothed and baleen whales present year-round or seasonally. This high cetacean biodiversity likely plays an important role in the structure, functioning and productivity of the ecosystem, and may increase trophic redundancy, thus contributing to food web resilience to disturbances. Methods Here we used stable isotope (δ13C and δ15N) analysis to characterize trophic niches, assess niche overlap, describe the trophic structure and discuss potential redundancy in the cetacean community. Using 407 samples from 12 species, we estimated Standard Ellipse Areas and overlaps between species and used a hierarchical clustering analysis to identify trophic guilds. Results and discussion δ13C and δ15N values ranged from -20.53 to -15.46‰ and from 7.78 to 14.41‰ respectively, suggesting the use of diverse habitats and resources among cetacean species. Clustering analysis revealed that species were grouped into four trophic guilds, segregated mainly by trophic position (TP): a low-TP guild with three zooplanktivore baleen whales, a mid-TP guild with micronektivores, a high-TP guild with micronekton and nekton consumers, and a cluster with only Pseudorca crassidens. There was significant isotopic niche overlap between one pair of species within each guild, indicating some potential for trophic redundancy in the community. Yet, these pairs also showed some form of spatial or temporal partitioning, suggesting that mechanisms promoting species coexistence could play a key role in structuring the cetacean community in the region and in its ecological role.